2020
DOI: 10.1073/pnas.2002817117
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between host genetics and gut microbiota determine susceptibility to CNS autoimmunity

Abstract: Multiple sclerosis (MS) is an autoimmune disease of the central nervous system. The etiology of MS is multifactorial, with disease risk determined by genetics and environmental factors. An emerging risk factor for immune-mediated diseases is an imbalance in the gut microbiome. However, the identity of gut microbes associated with disease risk, their mechanisms of action, and the interactions with host genetics remain obscure. To address these questions, we utilized the principal autoimmune model of MS, experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 99 publications
4
74
0
1
Order By: Relevance
“…However, it is critical to understand disease-specific probiotics. This paper, as well as well as another recently published paper, has identified L. reuteri as a detrimental organism that can contribute to CNS autoimmunity (1,18). L. reuteri can be found in several over-the-counter probiotics, raising the question of whether probiotics with L. reuteri are safe for MS patients.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…However, it is critical to understand disease-specific probiotics. This paper, as well as well as another recently published paper, has identified L. reuteri as a detrimental organism that can contribute to CNS autoimmunity (1,18). L. reuteri can be found in several over-the-counter probiotics, raising the question of whether probiotics with L. reuteri are safe for MS patients.…”
mentioning
confidence: 72%
“…The microbiome has recently been recognized as an environmental factor that contributes to MS. In Montgomery et al (1), the authors harnessed the natural genetic diversity between B6 mice, PWD/ PhJ (PWD) wild-derived mice, and a panel of 27 B6.Chr PWD consomic mice to investigate gene plus microbiome interactions. They identified chromosomes that affected disease susceptibility and also identified microbes that increased disease severity in disease-susceptible hosts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that Prevotella histicola suppresses EAE through Tregs ( 96 ), while Lactobacillus reuteri exacerbates the disease through pathogenic CD4 + and CD8 + T cell responses ( 97 ). The prophylactic administration of individual lactobacilli strains reduces EAE severity through diminished myelin oligodendrocyte glycoprotein (MOG)- T cell reactivity ( 98 ).…”
Section: Gut Microbiota and Cns Inflammatory Demyelinationmentioning
confidence: 99%